Tech for all : moving beyond the digital divide - Comito, Lauren (Lanham : Rowman & Littlefield, 2018)
'This book examines how the unequal distribution of resources between communities can limit access to emerging technologies. It gives real world examples of libraries going the extra mile to bring more than just email access to their communities, regardless of economic status or geographic distribution'--
Includes bibliographical references and index.
Keywords: Public access computers in libraries; Internet access for library users; Makerspaces in libraries; Digital divide; Computer literacy; Internet literacy